Box-jenkins methodology as an effective econometrics method for predicting energy consumption - Case Study of oil and gas consumption in Algeria - Atrousse, Souheila; Benzaou, Abderazak; Atrousse, Sabrina (Finance and Business Economies Review, 2019)
In this paper we aim to highlight the energy and its various sources because of its importance in all sectors and we also aim to highlight the most important source of non-renewable energy, namely petroleum and gaz, and this is due to the increase in consumption, especially in recent times, which led specialists to search for methods that allow us to study the amount of their consumption and predict their future values and this in order to obtain results close Very fact. To achieve this, we have implemented the Box-Jenkins methodology with its different stages on the time series annual consumption of gas and petroleum in Algeria in order to obtain an econometrics model we found that the methodology is a successful econometrics method that allows drawing up future plans and strategies as well as appropriate and timely measures and decisions.